A checklist of the New World species of Tillinae (Coleoptera: Cleridae), with an illustrated key to genera and new country records - Burke, Alan F.; Leavengood, Jr., John M.; Zolnerowich, Gregory (Zootaxa, 2015)
This checklist presents the distribution of the checkered beetle subfamily Tillinae (Coleoptera: Cleridae) in the New World. Information for 164 species and 2 subspecies from 11 genera is included. The data are based on an extensive survey of material collected throughout the Americas, descriptions of new species, a number of revisionary works, data from museum specimens, as well as unpublished checklists. Cymatodera, the most speciose tilline genus in the New World, has its greatest diversity in Mexico where 100 of the 134 recognized species are known to occur. Remaining genera inhabiting the New World and corresponding species numbers are: Araeodontia, 5 species; Barrotillus, 1 species; Bogcia, 2 species; Bostrichoclerus, 1 species; Callotillus, 5 species; Cylidrus, 1 species; Cymatoderella, 3 species; Lecontella, 3 species; Monophylla, 4 species; and Onychotillus, 5 species. An illustrated key to the genera of the New World Tillinae is provided. Forty-eight new country records are given for 35 species. References are presented for all species listed. Distribution maps for all New World genera are provided and locality data is presented for selected species.